التحليل القياسي للمتغيرات الاقتصادية المؤثرة على الاستثمار والاستثمار الزراعي في سورية (Latakia University Journal -Biological Sciences Series, 2017)
يركّز البحث في مطالبه على دراسة تطور الاستثمار الإجمالي، والاستثمار الزراعي ومعرفة طبيعة التغيرات الحاصلة خلال المدة (2000-2011)، وتقويم أداء الاقتصاد السوري، وقدرته على جذب الاستثمارات من عدمه، بالإضافة إلى تحليل العوامل المؤثرة على الاستثمار الإجمالي، والاستثمار الزراعي في سورية، باستخدام المنهج الوصفي التحليلي، والتحليل الكمي القياسي. وكان من أهم النتائج التي توصّل إليها البحث: أنّ معدل النمو السنوي لصافي ميزان المدفوعات سالبًا بنحو- 18.35 % والذي سيترتب عليه تدهور قيمته من عام لآخر، كما تبين من معاملات المرونة الكلية لدالة الاستثمار الاجمالي أنّ زيادة قيمة كل من الصادرات الكلية (X1)، والاحتياطات الأجنبية ( X3)، والعجز في الموازنة العامة للدولة ( X8) بنسبة 1% يمكن أن تؤدي معًا إلى زيادة الاستثمار الإجمالي بنسبة 3.5%، في حين بينت معاملات المرونة الكلية لدالة الاستثمار الزراعي أنّ زيادة كل من قيمة الصادرات الاجمالية إلى الناتج القومي الإجمالي ( X2)، والاحتياطات الأجنبية ( X3)، وصافي ميزان المدفوعات (X6) بنسبة 1% يمكن أن تؤدي معًا إلى زيادة الاستثمار الإجمالي بنسبة 22.3%، وتعدّ المتغيرات السابقة من أهم العوامل المحدّدة والموجّهة للاستثمار الاجمالي، والزراعي في سورية. وبناء عليه يتطلب من الاقتصاد السوري من أجل زيادة استثماراته تهيئة المناخ الاقتصادي، والسياسي للاستثمار، والتنمية الاقتصادية.The research focuses on the demands on the study of the total investment evolution, agricultural, investment and knowledge of the nature of the changes taking place during the period (2000-2011), and evaluate the performance of the economy and its ability to attract investments from the lack of it, in addition to the analysis of the factors affecting the total investment, agriculture and investment in Syria. Using descriptive and analytical approach, and quantitative analysis of the record, and it was the most important findings: that the annual growth of the net balance of payments is negative rate and the rate of 18.35-%, which will result in the deterioration of its value from year to year, as demonstrated by the total flexibility to function total investment transactions that increase the value of both exports College (x1), and foreign reserves (X3), and the deficit in the state budget (X8) 1% can lead both to increase the total investment by 3.5%, in total flexibility transactions to function agricultural investment showed that the increase in the value of each of the total exports GNP (X2), and foreign reserves (X3), the net balance of payments (X6) 1% can lead both to increase the total investment by 22.3%, and is the former variables of the most important determinants-oriented investment product and agriculture in Syria. Accordingly it requires the Syrian economy in order to increase its investments create the economic climate, and political investment and economic development.